Analisis Kualitas Layanan Digital Tata Usaha Berdasarkan Persepsi Mahasiswa Menggunakan Pendekatan WebQual 4.0 - Noviana Puspa Dewanty; M. Nabhan Adillah Haidar; Ria Octaviani Ningrum; Aulia Luthfi Salsabilla; Handika Nabila Karunia Putri; Joko Tri Nugraha (ANTASENA: Governance and Innovation Journal, 2026)
This study aims to analyze the quality of digital administrative services using the WebQual 4.0 approach based on students’ perceptions. The study employed a quantitative method through the distribution of questionnaires to 96 students of the Faculty of Social and Political Sciences, Universitas Tidar, who had previously used digital administrative services. The research instrument was designed using a 1–5 Likert scale to measure the three main dimensions of WebQual 4.0, namely usability, information quality, and service interaction quality. The results indicate that the overall quality of digital administrative services falls into the “good” category. The usability dimension obtained the highest score, particularly in terms of ease of access to service contacts, navigation functions, and website loading speed. In addition, the quality of service interaction was also considered good due to the use of multi-channel communication media, such as WhatsApp and websites, which facilitated communication between students and administrative staff. However, the information quality dimension still showed several weaknesses, especially regarding the relevance and completeness of the information provided to students. These findings indicate that digital administrative services should not only be supported by user-friendly systems, but must also provide clear, relevant, and user-oriented information. Therefore, the development of digital administrative services is expected to serve as an evaluation material for improving more effective, responsive, and student-oriented administrative services in the era of higher education digital transformation